Characteristics and significance of "green snake" bites in Myanmar, especially by the pit vipers Trimeresurus albolabris and Trimeresurus erythrurus. (November 2021) - Thein, Myat Myat; Rogers, Caitlyn A.; White, Julian; Mahmood, Mohammad Afzal; Weinstein, Scott A.; Nwe, Myat Thet; Thwin, Khin Thida; Zaw, Aung; Thant, Myo; Oo, Sai Sein Lin; Gyi, Khin Maung; Warrell, David A.; et al.
Abstract: Snakebite is an important problem in Myanmar. Regionally, bites by Eastern Russell's vipers, Daboia siamensis (Viperidae, Viperinae), and monocled cobras, Naja kaouthia are considered medically important, but those categorised as "green snake" bites are not. However, these may include bites by green pit vipers, Trimeresurus spp. (Viperidae, Crotalinae) for which no antivenom is available in Myanmar. Elsewhere in Southeast Asia, these snakes are reported to cause local and systemic envenoming. As part of the Myanmar Snakebite Project, prospective case data were collected over 3 years from five hospitals in the Mandalay region. These included 3803 snakebite cases reported from Mandalay region. Of these, 355 were listed as bites by a witnessed green-coloured snake. In 22 cases, the snakes responsible were retained and preserved, then expertly identified; 21 were medically important white-lipped pit vipers ( Trimeresurus albolabris ), and one as an Asian vine snake, Ahaetulla prasina (Colubridae, Ahaetuliinae) which is not of medical importance. Among confirmed Trimeresurus albolabris bites, 15/21 developed swelling of the bitten limb, and 3/21 coagulopathy, defined as a positive 20-min whole blood clotting test (20WBCT). None developed necrosis, blistering, thrombocytopenia or acute kidney injury (AKI). Of the remaining 333 patients bitten by green snakes that were not specifically identified, 241 (72%) developed swelling of the bitten limb, and 62 (19%) coagulopathy. AKI occurred in 21/333 patients, but only one required dialysis. At least 10/21 of the cases with AKI in this study were more likely to represent bites from Trimeresurus spp . than D. siamensis because the snake responsible was brought into the hospital, examined and described by the treating physician as "green-coloured". This study describes a previously unpublished case of AKI from envenoming by T. erythrurus in Yangon, and reviews cases of AKI following bites by this species and T. albolabris in Myanmar. This confirms that, at least on rare occasions, Trimeresurus spp . envenoming can cause AKI. This has important implications for snakebite management in Myanmar as the finding of local swelling, coagulopathy and AKI is generally considered pathognomonic of D. siamensis envenoming. Further collection of confirmed Trimeresurus spp. bites is required in Myanmar in order better to define the syndrome of envenoming and to assess the possible need for antivenom against Trimeresurus spp. in this country. Highlights: 3/21 patients envenomed by Trimeresurus albolabris developed coagulopathy. Trimeresurus spp. envenoming can cause acute kidney injury occasionally requiring haemodialysis. Verified identification of snakes presented with bitten patients prevents unnecessary antivenom use.